Reverse engineering study of diamond coated router bit using SEM and EDS method / Liew Fiji Kiew ... [et al.] - Liew, Fiji Kiew; Liew, Yit Lian; Awang Hashim, Dayang Maryani (2009)
Router bit is the most critical material during printed circuit board (PCB) depanelization process. Industrial records showed that replacing ordinary router bit with diamond coated router bit can save 80% of the depanelization cost. Hence, the quality and reliability of diamond router bit become a critical issue during material qualifying process. Without diamond coating detail, the quality and reliability of diamond coated router bit cannot be compared in future. A study on the diamond coated structure and the layer of coating of commercial diamond coated router bit is carried out to obtain information on the thickness, layer structures and types of diamond coating. The sample was prepared by etching using Murakami solution and an acid solution of hydrogen peroxide. The sample is analyzed under 5000X magnification of Scanning Electron Microscopy (SEM) to provide details on coating. The SEM results showed that there were two coating layers within the diamond coated layer. The total diamond coated layer was between 11.5-12.0 .The energydispersive X-ray spectrometry (EDS) provides the detail of material content. The type of coating was plasma-assisted chemical vapor deposition coating which involved pre-deposit layer. The Interlayer diamond coated film confirms has polycrystalline cubic boron nitride (PcBN) structure.